Studi Perbandingan Kewenangan Antara MK Indonesia Dengan MK Korea Selatan Terkait Dengan Impeachment Presiden - Wahyu Bingar Surahman (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Impeachment is carried out by authorized institutions against the president for alleged violations. The purpose of this writing is to compare impeachment in Indonesia and South Korea. To find out whether the impeachment process in Indonesia is possible to implement. Looking at the reasons for the dismissal of the President, South Korea has differences with Indonesia regarding the constitution. The process of dismissing the President in Indonesia needs to be reorganized and revised again regarding the correct regulatory provisions and in accordance with the concept of a country that adheres to and upholds democratic legal principles